2020
DOI: 10.1002/ente.201901260
|View full text |Cite
|
Sign up to set email alerts
|

Reversible High Capacity and Reaction Mechanism of Cr2(NCN)3 Negative Electrodes for Li‐Ion Batteries

Abstract: A detailed study of the electrochemical reaction mechanism between lithium and the trivalent transition‐metal carbodiimide Cr2(NCN)3, which shows excellent performance as a negative electrode material in Li‐ion batteries, is conducted combining complementary operando analyses and state‐of‐the‐art density functional theory (DFT) calculations. As predicted by DFT, and evidenced by operando X‐ray diffraction and Cr K‐edge absorption spectroscopy, a two‐step reaction pathway involving two redox couples (Cr3+/Cr2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Transition metal carbodiimide/cyanamide materials (TMC) belong to a type of transition metal compound system with a generic formula M x (NCN) y . , In these materials, metal atoms form coordination bonds with nitrogen atoms (−NCN−) 2– in organic diimine groups. Dronskowski’s group has contributed significant research achievements on the exploration of M x (NCN) y systems (including Cr 2 (NCN) 3 , , MnNCN, FeNCN, CoNCN, NiNCN, PbNCN, and other ternary systems , ). They revealed that the diimine group in TMC was considered to be an effective replacement for O 2– in transition metal oxides, clearly presenting an organo–inorganic hybrid structure of transition metal compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metal carbodiimide/cyanamide materials (TMC) belong to a type of transition metal compound system with a generic formula M x (NCN) y . , In these materials, metal atoms form coordination bonds with nitrogen atoms (−NCN−) 2– in organic diimine groups. Dronskowski’s group has contributed significant research achievements on the exploration of M x (NCN) y systems (including Cr 2 (NCN) 3 , , MnNCN, FeNCN, CoNCN, NiNCN, PbNCN, and other ternary systems , ). They revealed that the diimine group in TMC was considered to be an effective replacement for O 2– in transition metal oxides, clearly presenting an organo–inorganic hybrid structure of transition metal compounds.…”
mentioning
confidence: 99%
“…In recent years, several studies on carbodiimides materials used in battery systems have been successfully carried out, , exhibiting great potential application in energy storage fields. Nevertheless, many of these studies include strict preparation conditions (Schlenk technique) ,, or multistep (both liquid and solid reactions) , synthesis techniques, bringing forward difficulties for further structural design of metal carbodiimide materials.…”
mentioning
confidence: 99%
“…When metal carbodiimides are applied in LIBs, most of them exhibit high theoretical capacity, poor conductivity, and low initial Coulombic efficiency, which is similar to the oxides. Meanwhile, the researchers find that they show obviously different electrochemical properties due to the variation of metal. , Sougrati et al prepared FeNCN microparticles as anode that showed the reversible capacities of 600 and 400 mAh g –1 at 56 mA g –1 and a high initial Coulombic efficiency of ≥95% in lithium/sodium ion battery . Eguia-Barrio and co-workers designed CuNCN microflowers and ZnNCN microparticles by soft chemistry method, and they exhibited the volume expansions of 78% and 54%, respectively, and the discharging capacity of about 200 mAh g –1 at 52 mA g –1 .…”
mentioning
confidence: 99%
“…1371 cm − 1 can be related to the asymmetric -N = C = N-stretching mode (Fig. 2b) [40]. The peaks at ca.…”
Section: Resultsmentioning
confidence: 94%